Release Behavior of the Pineal Hormone Melatonin from Modified Matrix Tablets Based on Poly(L-Lactic Acid) and Its Derivatives - Marilena Vlachou; Georgios-Marios Bolbasis; Anna-Evaggelia Trikali; Chrystalla Protopapa; Angeliki Siamidi; Aikaterini Sakellaropoulou; Evi Christodoulou; Nikolaos D. Bikiaris (Applied Sciences, 2025)
Biodegradable polyesters have been researched intensively over the last two decades because of their biodegradability and superb physical properties. However, the use of linear biodegradable polyesters, for the preparation of drug delivery systems (DDS), is hampered by several limitations. In view of this, scientific attention has been shifted to the employment of branched-chain (co-)polymers. In this context, we present herein the development of new melatonin (MLT) tablet formulations, using novel branched polylactide (PLA)-based copolymers of different architectures. Specifically, three PLA-polyol branched polyesters, namely, a three-arm copolymer based on glycerol (PLA-glycerol), a four-arm copolymer based on pentaerythritol (PLA-pentaerythritol), and a six-arm copolymer based on sorbitol (PLA-sorbitol), were utilized. The presence of these polyesters in the formulations was found to be crucial, as the sought MLT release, regarding its use in confronting sleep onset and/or sleep maintenance dysfunctions, was achieved. The copresence of the other excipients in the matrix tablets (lactose monohydrate, hydroxypropylmethylcellulose, microcrystalline cellulose, and sodium alginate) led to a concentration-dependent synergistic effect on the MLT release. To the best of our knowledge, this is the first investigation with these specific polymeric materials, concerning MLT modified release from matrix tablets.